Hukum Internasional Pasca Perang Irak: Legalisasi Politik Internasional dan Politisasi Hukum Internasional - Jailani, Abdulkadir (UI Scholars Hub, 2005)
The United Nations’s to prevent invasion to Iraq and United States’ occupatin with it allies have cause the pessimism to the future of international law. The international community is worried about the unilateralism tendency by the United States because it can threaten the rule law’s future in international relation. So many questions about the existence of international law and its nature such as whether international will be merely as the means of power only. This article tries to answer those questions with special approach (critical legal studies).